If log(p+r)+log(p+r-2q)=2log(p-r) then p, q and r are in
A. AP
B. GP
C. HP
D. None of these
Answer
Verified
466.5k+ views
Hint: In order to solve this problem you need to use the property of logarithm. That is log(ab)=loga + logb and $a\log b = \log {b^a}$ then we will be getting the equations solving those equations and knowing the properties of HP you will get the right answer.
Complete step-by-step answer:
It is given that, log(p+r)+log(p+r-2q)=2log(p-r)
We have to use property of logarithm log(ab)=loga + logb and $a\log b = \log {b^a}$
Now, using above identity we can write log(p+r)+log(p+r-2q)=2log(p-r) as
$\log ((p + r)(p + r - 2q)) = \log {(p - r)^2}$
On cancelling log from both sides we get the equation as,
$
\Rightarrow (p + r)(p + r - 2q) = {(p - r)^2} \\
\Rightarrow {p^2} + pr - 2qp + pr + {r^2} - 2pr \\
$
Now, ${p^2}$ and ${r^2}$ are cancelled,
Then the equation will become,
2pr – 2pq – 2qr = -2pr
4pr = 2pq + 2qr
On dividing this equation by 2pqr we get,
$ \Rightarrow \dfrac{2}{q} = \dfrac{1}{p} + \dfrac{1}{r}$
This condition shows that p, q, r makes an HP where the above condition is the harmonic mean of the HP p, q, r.
Now, we can easily see p, q, r is in HP.
So, the correct answer is “Option C”.
Note: Whenever we face such types of problems we use some important points. Like always trying to remove log from both sides of the equation by using the identity of logarithm then after some easy rearrangement we can easily identify which type of progression formed.
Complete step-by-step answer:
It is given that, log(p+r)+log(p+r-2q)=2log(p-r)
We have to use property of logarithm log(ab)=loga + logb and $a\log b = \log {b^a}$
Now, using above identity we can write log(p+r)+log(p+r-2q)=2log(p-r) as
$\log ((p + r)(p + r - 2q)) = \log {(p - r)^2}$
On cancelling log from both sides we get the equation as,
$
\Rightarrow (p + r)(p + r - 2q) = {(p - r)^2} \\
\Rightarrow {p^2} + pr - 2qp + pr + {r^2} - 2pr \\
$
Now, ${p^2}$ and ${r^2}$ are cancelled,
Then the equation will become,
2pr – 2pq – 2qr = -2pr
4pr = 2pq + 2qr
On dividing this equation by 2pqr we get,
$ \Rightarrow \dfrac{2}{q} = \dfrac{1}{p} + \dfrac{1}{r}$
This condition shows that p, q, r makes an HP where the above condition is the harmonic mean of the HP p, q, r.
Now, we can easily see p, q, r is in HP.
So, the correct answer is “Option C”.
Note: Whenever we face such types of problems we use some important points. Like always trying to remove log from both sides of the equation by using the identity of logarithm then after some easy rearrangement we can easily identify which type of progression formed.
Recently Updated Pages
Master Class 10 General Knowledge: Engaging Questions & Answers for Success
Master Class 10 Computer Science: Engaging Questions & Answers for Success
Master Class 10 Science: Engaging Questions & Answers for Success
Master Class 10 Social Science: Engaging Questions & Answers for Success
Master Class 10 Maths: Engaging Questions & Answers for Success
Master Class 10 English: Engaging Questions & Answers for Success
Trending doubts
10 examples of evaporation in daily life with explanations
Distinguish between coming together federations and class 10 social science CBSE
List out three methods of soil conservation
Complete the following word chain of verbs Write eat class 10 english CBSE
Distinguish between aInland fishery and marine fishery class 10 biology CBSE
On the outline map of India mark the following appropriately class 10 social science. CBSE